Principal’s Readiness to Implement Deep Learning Program - Sulistyowati, Rachma; Santosa, Achadi Budi; Hasanah, Enung (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The implementation of deep learning has become a strategic priority for improving the quality of teaching and learning. The success of deep learning implementation is strongly influenced by the readiness of school principals as instructional leaders. This study aims to describe school principals’ readiness to implement deep learning program using a descriptive qualitative approach. Data were collected through interviews, observations, and document analysis, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that principals’ readiness is reflected in four core deep learning frameworks: pedagogical practices, learning environment, learning partnerships, and the use of digital technology. Principals demonstrate readiness through a clear understanding of deep learning concepts, support for teachers’ instructional innovation, the creation of collaborative learning environments, the strengthening of partnerships with parents and communities, and the integration of digital technology to support learning. However, challenges remain, particularly limited teachers’ digital competencies and insufficient cross-stakeholder collaboration. Principals’ readiness plays a crucial role in ensuring the successful implementation of deep learning and requires policy support, continuous professional development, and a strong learning ecosystem.